Optimasi Pemasaran UMKM di Dusun Kalirase, Trimulyo, Sleman - Al Azhar, Hafizh; Fitrianingsih, Ihtiara (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Dusun Kalirase is a region within Trimulyo Village, Sleman District, where the majority of residents are engaged in agriculture and plantations. Additionally, there exist several Micro, Small, and Medium Enterprises (MSMEs) - UMKM in Indonesian language - with significant potential, having yet to be optimally managed, particularly in terms of marketing. This community service initiative aims to address several major challenges faced by MSMEs in Dusun Kalirase, such as a lack of knowledge about digital marketing, non-strategic business locations, and insufficient promotional resources. Through the